A fundamental study on structural strength assessment of U-bolts for expanded application to shipbuilding and offshore piping systems - Minsung Chun; Jinyoung Kim; Kangho Kim; Daseul Jeong; Deokyeon Lee; Sungkuk Wi; Byeonghwa Kim; Cheonghak Kim; Chun-Sik Shim (International Journal of Naval Architecture and Ocean Engineering)
The currently defined Safe Working Load (SWL) of the U-bolt has been determined excessively conservatively. To address this issue, this study conducted structural tests and numerical analysis on round type U-bolts of various sizes. The structural tests were conducted using a 2.5 MN actuator at the SURF R&D center, and the strain was measured through a uniaxial strain gage. The test showed the failure load greatly exceeded the design load with horizontal force. This necessitates a reevaluation and redefinition of load standards. Nonlinear numerical analysis was carried out, and these results were compared with the structural test results. When subjected to vertical loading, behavior was similar to uniaxial tension. On the other hand, using linear elastic analysis for determining SWL for horizontal loading was found to be irrational. A methodology was proposed for estimating the SWL of the U-bolt.